2012
DOI: 10.1254/jphs.11r06fm
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Strategy for Amino Acid Medicine: Effects of Dietary Glutamate on Gut and Brain Function

Abstract: Abstract. The gustatory and visceral stimulation from food regulates digestion and nutrient utilization, and free glutamate (Glu) release from food is responsible for the umami taste perception that increases food palatability. The results of recent studies reveal a variety of physiological roles for Glu. For example, luminal applications of Glu into the mouth, stomach, and intestine increase the afferent nerve activities of the glossopharyngeal nerve, the gastric branch of the vagus nerve, and the celiac bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…The ECs of the gut mucosa are the predominant site for the synthesis and storage of 5-HT in humans (Gershon and Tack, 2007). The release of 5-HT occurs in response to chemical stimuli, e.g., the presence of nutrients (e.g., glutamate, glucose), or food-related/bacterial toxins in the intestinal lumen (Mayer, 2011; Kitamura et al, 2012). However, 5-HT produced by gut microbiota could possibly contribute to the overall 5-HT pool in the gut.…”
Section: Bacterial Production Of Neuroactive Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…The ECs of the gut mucosa are the predominant site for the synthesis and storage of 5-HT in humans (Gershon and Tack, 2007). The release of 5-HT occurs in response to chemical stimuli, e.g., the presence of nutrients (e.g., glutamate, glucose), or food-related/bacterial toxins in the intestinal lumen (Mayer, 2011; Kitamura et al, 2012). However, 5-HT produced by gut microbiota could possibly contribute to the overall 5-HT pool in the gut.…”
Section: Bacterial Production Of Neuroactive Moleculesmentioning
confidence: 99%
“…Multiple Glu receptor types (including ionotropic, types 1 and 4 metabotropic receptors and heterodimeric, TAS1R1 + TAS1R3, L -Glu taste receptors) have been detected in GI epithelial cells and/or enteric neurons in the stomach, small intestine and colon (Kondoh et al, 2009; San Gabriel et al, 2009; Kitamura et al, 2012). More in detail, mGlu 4 receptors have been detected in the mucosa of both the gastric antrum and duodenum (Akiba et al, 2009), while both mGlu 4 and mGlu 7 receptors have been identified in the colon epithelium (Chang et al, 2005; Julio-Pieper et al, 2010).…”
Section: Glu/gaba: Receptors Signaling and Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there is an operative amino acid sensing system within the gastric mucosa that recognizes dietary glutamate [89]. Albeit being the major excitatory neurotransmitter in the central nervous system, this amino acid also modulates important gut functions such as secretion, motility and metabolism [90] via mechanisms that include the generation of • NO and serotonin [91]. Given the high steady state concentrations of • NO achieved in the gastric lumen and mucosa upon nitrite reduction, glutamate-dependent pathways in the gastrointestinal tract are likely to be modulated by dietary nitrate.…”
Section: Redox Signaling By Nitrite and Nitric Oxide From Gut Mucosa mentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that 4 billion people, 80% of the world population presently used herbal medicine for some aspects of primary health care. As nutraceuticals or functional foods, plants possess some health promoting and or disease preventing property beyond the basic nutritional function of supplying nutrients (Kitamura et al, 2012). Studies have shown that consumption of many different wild plants as food provides nutritional benefits (Cook et al, 2000.…”
Section: Introductionmentioning
confidence: 99%